Пошаговое объяснение:
(5/7*4,2 - 5/7*14n) - (2,4*5/6m - 2,4*5n) =
(5/7*4 2/10 - 5/1 * 2n) - (2 4/10*5/6m - 2 4/10*5n) =
(5/7 * 42/10 - 10n) - (24/10*5/6m - 24/10*5n) =
(3 - 10n) - (2m - 12n) =
3 - 10n - 2m + 12n =
3 + 2n - 2m
3 + (2*5) - (2*(-2) ) =
3 + 10 + 4 = 17
ответ : 17
Пошаговое объяснение:
(5/7*4,2 - 5/7*14n) - (2,4*5/6m - 2,4*5n) =
(5/7*4 2/10 - 5/1 * 2n) - (2 4/10*5/6m - 2 4/10*5n) =
(5/7 * 42/10 - 10n) - (24/10*5/6m - 24/10*5n) =
(3 - 10n) - (2m - 12n) =
3 - 10n - 2m + 12n =
3 + 2n - 2m
3 + (2*5) - (2*(-2) ) =
3 + 10 + 4 = 17
ответ : 17